Analisis Swot Strategi Pengembangan Asuransi Syariah Bumiputera di Aceh - Nilam Sari; Hafiizh Maulana; Mirza Frananda Kusuma (Jurnal Ilmiah Ekonomi Islam, 2021)
The study, entitled "Strategy for the Development of Bumiputera Syari'ah Insurance in Aceh, 2016-2018 (SWOT Analysis Approach)", aims to find out the development of Bumiputera Islamic insurance in Aceh Province and the strategy for developing the Syari'ah Bumiputera insurance in Banda Aceh City. This study uses a non-experimental quantitative descriptive approach. Data collection techniques by interview and documentation. Data analysis using SWOT analysis. Based on the research results, it is known that the potential of PT. In terms of strength, the Banda Aceh branch of Syari'ah Bumiputera Insurance is the principle of non-usury, the network is online, the general takaful is full of sharia, the brand is stronger as sharia insurance than other sharia insurance companies, the policy is quickly completed and the claims service is served well. Opportunities are that the majority of Banda Aceh's residents are Muslim, sharia banking is growing and advances in technology (internet). Constraints owned by PT. In terms of weaknesses, the Banda Aceh branch of Syari'ah Bumiputera Insurance is that the market share of Islamic insurance in Aceh is still low and quality human resources are still limited. Threats are the amount of competition in the insurance industry, then a lack of public understanding of the capital regulation syari'ah insurance. Strategies that can be implemented or utilized by PT. Asuransi Syari'ah Bumiputera Banda Aceh branch is a strategy of Strengths Opportunities. The strategy is to optimize the coverage area with agent support, increase and maintain cooperation with the syari'ah banking industry and increase flexibility in the claim processing mechanism.